Elbow joint position and hand pressure force sense under conditions of quick reaction in table tennis players - Bańkosz, Ziemowit (Array, 2021)
Joint position sense and force reproduction are the most commonly used measures of proprioception. It is interesting to measure proprioception in integration of the factors most commonly viewed as the most important in table tennis—speed, in particular quick reaction. The aim of this study was to evaluate the accuracy of replication of a specific range of motion and force of hand pressing under conditions of limited time. Forty table tennis players and 30 non-athletes participated in the study. Electrogoniometric and dynamometric methods were used in the investigation. The accuracy of replication of pronation and supination movements of the forearm at the elbow joint and force of hand pressing under conditions of limited time (performing the activity as fast as possible in response to visual signals) were measured. The tests performed in the study revealed that both female and male table tennis players were characterized by a higher level of forearm position sense during performing the fastest possible pronation and supination movements in most of the tasks. Better results of table tennis players than of the control group suggest that joint position and hand pressure sense integrated with quick reaction are important performance factors in table tennis. The results also indicate opportunities for using this methodology to monitor training.